Landscapes of resistance: Tibetan modernity and the online politics of representation in contemporary China - Kehoe, Séagh (2019)
This thesis examines the online politics of representation surrounding Tibetan modernity in contemporary China. Contextualised within the rapid modernisation that has characterised the Great Western Development Campaign (xibu da kaifa西部大开发), I focus on Chinese state media and Tibetan discourses relating to material transformation, economic development and cultural commercialisation, and historical progress. I use Critical Discourse Analysis to analyse the ways in which the state harnesses the speed, scope, and scale of online media to frame and communicate representations of Tibetan modernity to audiences across China. I argue that this functions as a form of cultural governance, deploying a set of representational strategies across diverse cultural fields in order to manage public discourse about Tibet and consolidate state authority, legitimacy, and sovereignty. I also examine how Tibetans use online spaces to produce counter discourses in order to challenge official representations and generate new public understanding about life in contemporary Tibet. I describe how notions of homeland form a core part of this process, functioning as a discursive practice that mobilises various cultural and spiritual attachments to Tibet in order to decentre state place-making practices, reaffirm a distinctly Tibetan territory, and disrupt the prevailing hegemonic representations of Tibetan modernity across Chinese state media. In doing so, I advance a new theoretical approach that explains homeland as a discursive practice that is embedded and mobilised within broader social, cultural, political, and economic relations in order to effect political change.